STUDI PERENCANAAN TRAFFIC LIGHT SIMPANG JALAN AMBE NONA – OPU TO SAPPAILE – BATARA, KOTA PALOPO - -, Hasbi (Jurnal Ilmiah Ecosystem, 2016)
This study aimed (1) to observe the average daily traffic (LHRT) at signalized intersections, (2) analyzing traffic light control system (planning traffic light). The research is the study of the characteristics of the traffic light (traffic light planning). Approach the research methods used in this research is analytical and descriptive quantitative method. The results of the analysis and discussion shows that the traffic volume of the average daily (LHRT) at the signalized intersection leg intersections observed has been eligible to planned needs traffic light (planning traffic light), and the analysis cycle time according to the actual conditions of the existing traffic on when done from the north, south, east and west.